An exploratory study of the governance and management processes of family foundations in South Africa - Najjaar, Sufiya (Department of Social Development, 2020)
Family foundations are important vehicles that make a positive impact in society both locally and globally and can be a unifying force in which family members can work together for a common altruistic purpose. The same governance and management principles that are applied by families in family businesses should also pertain to family foundations. In the United States (U.S.) there exists various organisations that serve to guide family foundations with best practices on foundation governance and management principles. In South Africa much less information is available to family foundations. This research study explores the governance and management processes of family foundations in South Africa. I reviewed extensive literature on the governance structures and management processes of family foundations particularly in the U.S. Based on the literature review and the research questions, a suitable research methodology was selected. A convergent parallel mixed method approach was used. Ethics clearance was obtained from the University of Cape Town and a sample of ten family foundations was purposively selected to be part of the study. Data was collected from 15 respondents, eight of whom were non-family members and seven were family members related to the founding donor. A semi-structured interview schedule was used and the same research participants completed a survey. The data was analysed using Tesch's (1990) adaptation for data analysis. The contribution that this study makes is an enhanced understanding of the governance and management processes of family foundations in South Africa and the challenges that some face in this regard. The study makes a number of findings including: Family foundations felt that the fiduciary duties and responsibilities, fiscal oversight and internal controls were duly executed. Family foundations were satisfied that the board knew enough about investment principles, however environmental, social and governance (ESG) practices was not high on the agenda for most family foundations; family foundation boards were diverse in terms of gender, age, expertise and experience but were not racially diverse; in some instances there was conflict between family members but this did not stand in the way of foundation performance; decision making was collaborative and most often made by consensus; legacy was not important for all family foundations. Most family foundations thought they had a clear grant making strategy with some family foundations including newer generations values and ideas into grant making. Based on these findings, the research study concludes by making recommendations for family foundations to improve governance and management processes.